2020
DOI: 10.1242/jeb.214171
|View full text |Cite
|
Sign up to set email alerts
|

The reptilian perspective on vertebrate immunity: 10 years of progress

Abstract: Ten years ago, ‘Understanding the vertebrate immune system: insights from the reptilian perspective’ was published. At the time, our understanding of the reptilian immune system lagged behind that of birds, mammals, fish and amphibians. Since then, great progress has been made in elucidating the mechanisms of reptilian immunity. Here, I review recent discoveries associated with the recognition of pathogens, effector mechanisms and memory responses in reptiles. Moreover, I put forward key questions to drive the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 141 publications
3
36
0
Order By: Relevance
“…The so‐called adaptive phase, in turn, confers immunological memory resulting from the production of specific antibodies by B lymphocytes (Chen & Robert, 2011; Robert, 2017). There are some differences between endotherms and ectotherms, such as the types of cytokines expressed (Zimmerman et al, 2014; Zimmerman, 2020) and the lymphoid tissue organization (Neely & Flajnik, 2016; Zimmerman, 2020).…”
Section: Ecthoterms Immunity—a Short Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The so‐called adaptive phase, in turn, confers immunological memory resulting from the production of specific antibodies by B lymphocytes (Chen & Robert, 2011; Robert, 2017). There are some differences between endotherms and ectotherms, such as the types of cytokines expressed (Zimmerman et al, 2014; Zimmerman, 2020) and the lymphoid tissue organization (Neely & Flajnik, 2016; Zimmerman, 2020).…”
Section: Ecthoterms Immunity—a Short Reviewmentioning
confidence: 99%
“…The complement cascade is mediated by proteins and has three pathways: classical, lectin, and alternative, each triggered by a distinct molecule‐binding receptor. Independently of the activated pathway, the outcome is the inflammation signaling, opsonization, and membrane attack complex resulting in microbial cell death due to leakage of intracellular contents and membrane lysis (Magnadóttir, 2006; Rodriguez & Voyles, 2020; Zimmerman, 2020). In this SI, Rodriguez and Voyles (2020) bring evidence that the complement system is essential for pathogen clearance and is an important immune defense system, especially in amphibians infected by the fungus Batrachochytrium dendrobatidis .…”
Section: Ecthoterms Immunity—a Short Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, researchers failed to identify the SOCS homologue in ctenophores and choanoflagellates, but could identify homologues of six SOCS gene members in Porifera (Liongue, Taznin & Ward, 2016). However, recent studies on reptiles have shown that their immune systems tend to have similar components to their mammalian counterparts with subtle differences (Zimmerman, 2020). We hypothesized that, similar to mammals, the SOCS family of reptiles followed classical expansion during the two rounds of whole-genome duplication with intact SOCS family members.…”
Section: Introductionmentioning
confidence: 98%
“…The SOCS sequences extracted from reptilian genomes and those from public resources provided us with an excellent opportunity to explore reptile evolutionary selection diversity. Reptiles, the only ectothermic amniotes, have wide ranges of habitat, modes of diet, behaviors, lifespans, and reproduction (Zimmerman, 2020). It has been demonstrated that reptile body temperature cannot be kept constant and will undergo seasonal shifts with environmental temperature, and infection is strongly related to body temperature (Zimmerman, Vogel & Bowden, 2010).…”
Section: Introductionmentioning
confidence: 99%